Medicinal plants and their use by an ethnic minority Jirel in Dolakha district, Central Nepal - Karki, Sangram; Prakriti Dhital, Ashis; Uprety, Yadav; Ghimire, Suresh Kumar (Ethnobotany Research and Applications, 2023)
Background: Plants are important source of traditional medicine and are used widely in the primary healthcare of indigenous peoples and local communities. Despite a considerable number of ethnobotanical studies in Nepal, there are still several regions to be explored and scientifically document the traditional uses of medicinal plants. This study was conducted in one of such areas in the Dolakha district of central Nepal with the indigenous Jirel community. Methods: Ethnobotanical information was collected using guided field walks, semi-structured interviews, and key informant interviews with traditional herbalists and elderly men and women of the Jirel community. The data were analyzed both qualitatively and quantitatively using use value (UV), informant consensus factor (FIC), and preference ranking. Results: This study recorded 111 medicinal plant species belonging to 103 genera that were used to treat 11 health disorders. Families such as Asteraceae, Lamiaceae, and Rosaceae have contributed a higher number of species of the total species recorded. Gastrointestinal disorders, skeleton-muscular disorders, fever, headache and cut and wounds were the common health problems among the Jirel people. Roots were mostly used for the preparation of remedies, followed by leaves and fruits. The informant consensus factor (FIC) ranges from 0.74 to 0.93 with an average of 0.87. Paris polyphylla, Cirsium verutum, and Astilbe rivularis have the highest use values of 0.98, 0.96 and 0.92 respectively. This research finds that traditional knowledge about the use of medicinal plants is more centered on Jirel herbal healers (Lama/Jhakris) and elderly people than youths. Similarly, knowledge transmission routes are mainly from parents to their eldest child. Over-harvesting, premature harvesting, and deforestation were found as major threats to medicinal plants. Furthermore, the abandonment of traditional herbal practices, the loss of traditional healers, and the youth’s unwillingness to traditional healing systems were threats to the ethnobotanical knowledge of medicinal plants in the Jirel community. Conclusions: The diversity of medicinal plants in the area and the associated indigenous knowledge of use among Jirel people have contributed significantly to their healthcare system. The medicinal uses of the documented species provide the primary information for further ethnopharmacological studies and conservation of most useful species in the study area. Keywords: Ethnobotany, Traditional knowledge, Informant consensus factor, Knowledge transmission, Preference ranking, Use value